Modulation of semiconductors with transition metals: morphological, optical, and electronic properties - Patrocinio, Katiana Lima do (2024)
Research on semiconductors has been of great interest due to their numerous applications. These materials are versatile, and doping, which introduces impurities into the crystal structure, is a common strategy that can enhance their properties. This process directly influences the electronic, optical, and morphological properties, allowing for adjustments to optimize the effectiveness of semiconductors in specific applications.This process directly influences the electronic, optical, and morphological properties of semiconductors, enabling adjustments to optimize their effectiveness for specific applications. Within this context, this study introduces two matrices: silver tungstate (α-Ag2WO4 or AW) and zinc germanate (Zn2GeO4 or ZGO), each dedicated to investigating the influence of doping with transition metals. For AW doped with vanadium at different concentrations (x = 0.0; 0.01; 0.02; and 0.04 mol%), it was demonstrated as a highly efficient catalyst for the oxidation of sulfides to sulfones under mild conditions, exhibiting high yields and selectivity. Sequestration experiments identified the direct involvement of electron-hole (e-/h+) pairs, hydroxyl radical (⦁OH), and singlet oxygen (1O2) in the oxidation process. Electron paramagnetic resonance (EPR) and X-ray photoelectron spectroscopy (XPS) analyses confirmed the presence of V4+ cations in the doped samples. Theoretical results suggested that the enhanced catalytic activity of vanadium-doped samples is associated with the predominant presence of the (100) surface morphology, indicating potential applications in sulfide oxidation reactions in the absence of light. For ZGO doped with nickel at different concentrations (x = 0, 0.01, and 0.16 mol%), doping was utilized to tailor its structural and electronic properties towards creating efficient blue pigments for ceramics. Density functional theory (DFT) calculations revealed that the 3d orbitals of Ni2+ generate new energy levels, altering the local electronic structure and resulting in electron transfer that produces the blue color. Analyses confirmed that this modification is responsible for the blue hue, while also highlighting the low toxicity and excellent chemical and thermal durability of the pigments. This work establishes a robust foundation for the design of adjustable and high-performance ceramic pigments. Ultimately, these materials demonstrate the potential of scientific research to drive significant innovations and improvements in real-world technologies and products.